Electrophysiological study of supraspinal input and spinal output of cat's subnucleus reticularis dorsalis (SRD) neurons. - Patricia Velo (Public Library of Science (PLoS), 2013)
This work addressed the study of subnucleus reticularis dorsalis (SRD) neurons in relation to their supraspinal input and the spinal terminating sites of their descending axons. SRD extracellular unitary recordings from anesthetized cats aimed to specifically test, 1) the rostrocaudal segmental level reached by axons of spinally projecting (SPr) neurons collateralizing or not to or through the ipsilateral nucleus reticularis gigantocellularis (NRGc), 2) whether SPr fibers bifurcate to the thalamus, and 3) the effects exerted on SRD cells by electrically stimulating the locus coeruleus, the periaqueductal grey, the nucleus raphe magnus, and the mesencephalic locomotor region. From a total of 191 SPr fibers tested to cervical 2 (Ce2), thoracic 5 (Th5) and lumbar5 (Lu5) stimulation, 81 ended between Ce2 and Th5 with 39 of them branching to or through the NRGc; 21/49 terminating between Th5 and Lu5 collateralized to or through the same nucleus, as did 34/61 reaching Lu5. The mean antidromic conduction velocity of SPr fibers slowed in the more proximal segments and increased with terminating distance along the cord. None of the 110 axons tested sent collaterals to the thalamus; instead thalamic stimulation induced long-latency polysynaptic responses in most cells but also short-latency, presumed monosynaptic, in 7.9% of the tested neurons (18/227). Antidromic and orthodromic spikes were elicited from the locus coeruleus and nucleus raphe magnus, but exclusively orthodromic responses were observed following stimulation of the periaqueductal gray or mesencephalic locomotor region. The results suggest that information from pain-and-motor-related supraspinal structures converge on SRD cells that through SPr axons having conduction velocities tuned to their length may affect rostral and caudal spinal cord neurons at fixed delays, both directly and in parallel through different descending systems. The SRD will thus play a dual functional role by simultaneously regulating dorsal horn ascending noxious information and pain-related motor responses.